EXPLORING STUDENTS' SELF-EFFICACY IN VOCABULARY AND PRONUNCIATION LEARNING THROUGH CULTURALLY RESPONSIVE DIGITAL GAME-BASED LEARNING - Anggreni Kaita Ana Wulang; I Putu Indra Kusuma; Ni Wayan Surya Mahayanti (RADJA PUBLIKA, 2026)
This study explores students’ self-efficacy in learning English vocabulary and pronunciation through Culturally Responsive Digital Game-Based Learning (CRDGBL) at SMP Negeri 1 Nggaha Ori Angu, East Sumba, Indonesia. The research was conducted to investigate how culturally integrated digital game-based instruction influences students’ language learning experiences and self-efficacy development. A basic qualitative research design was employed, involving seven seventh-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, activity logs, researcher field notes, and documentation and were analyzed thematically following Merriam and Tindell’s (2015) qualitative analysis procedures. The findings reveal that CRDGBL supported vocabulary learning by connecting learning materials to students’ local culture, enabling meaningful retention through contextualized and interactive activities. In pronunciation learning, repeated exposure to audio models, teacher guidance, and peer interaction gradually improved students’ accuracy and speaking confidence. Furthermore, students’ self-efficacy increased through mastery experiences, vicarious experiences, verbal persuasion, and positive emotional states during learning activities. Overall, the study demonstrates that integrating local cultural content into digital game-based learning creates an engaging and supportive environment that enhances both linguistic skills and learners’ confidence. These findings highlight the importance of culturally responsive and technology-enhanced pedagogy in rural EFL contexts to improve students’ English learning outcomes and self-beliefs.